Dynamic Policy Dalam Meningkatkan Blue Economy Di Desa Tertinggal - Ikhsan, Masrul; Nisaa, Fadhiilatun; Rahmanul, Rahmanul; Vani, Resa Vio (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
The blue economy concept is increasingly important in facing challenges in coastal areas, especially in underdeveloped areas such as North Rupat District, Riau Province. This research aims to analyze the role of dynamic policies in maximizing the potential of the blue economy and identify the inhibiting factors experienced. The method used is a qualitative approach with in-depth interviews. The research results show that responsive and flexible policies are needed to overcome various existing limitations, besides that the involvement of local communities in planning and managing marine resources is crucial for the success of the blue economy. Even though there is great potential in the fisheries and tourism sectors, challenges in infrastructure and technology are still the main obstacles in this regard.